Shedding light on the shadows: oxidative stress and its pivotal role in prostate cancer progression - Biesiadecki, Marek; Mołoń, Mateusz; Balawender, Krzysztof; Kobylińska, Zofia; Galiniak, Sabina (Frontiers in Oncology, 2024)
Objectives: Data on oxidative protein damage, total antioxidant capacity (TAC) and lipid peroxidation in progression of prostate cancer remain elusive. So far, the influence of the presence of perineural invasion on the level of oxidative stress has not been described. Additionally, there is limited data on the level of oxidative stress in patients’ urine. Methods: We compared the levels of oxidative stress markers in serum and urine in 50 patients with prostate cancer depending on the tumor stage and histological grade, the Gleason score, and the presence of perineural invasion. Results: We found a significantly de-creased level of serum thiol groups and TAC in participants with prostate cancer. Similarly, serum Amadori products and malondialdehyde (MDA) were higher in patients than in healthy men. There was a significantly decrease in TAC and a significantly increased MDA in the urine of prostate cancer patients. As the stage of cancer increased, a decrease in the thiol group concentration and TAC as well as an increase in the concentration of lipid peroxidation products in the serum was observed. The serum level of advanced oxidation protein products (AOPP) increased in the group with Gleason scores greater than 7. Furthermore, serum thiol groups and TAC were reduced in the group with Gleason >7 as compared to Gleason <7. The presence of perineural invasion significantly reduced serum and urinary TAC and increased urinary AOPP concentration. Conclusions: These results indicate a significant role for oxidative damage in prostate carcinogenesis and its progression. Characterizing oxidative and nitrosative damage to proteins may be useful in designing targeted therapies for prostate cancer patients.